2017
DOI: 10.13189/ujar.2017.050607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grass-legume Intercropping on Dry Matter Yield and Nutritive Value of Pastures in the Eastern Cape Province, South Africa

Abstract: The Eastern Cape Province, South Africa is faced with inadequate quantity of livestock feed especially during the drier (winter) seasons. Forage legumes were over sown into natural grasses to determine their potential to improve feed quality and quantity. Four forage legumes namely: Trifolium vesiculosum (Arrowleaf clover), Lespedeza cuneata (sericea lespedeza) , Trifolium repens (white clover) and Lotus corniculatus (birdsfoot trefoil) were intercropped with native grasses in the old arable land located in Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…Although Desmanthus contributed a small proportion of initial pasture biomass (11.5%) in the study, pasture DM yield was 443 kg/ha higher in the Desmanthus paddock compared to the buffel-grass-only paddock. This finding agrees with other studies that reported an increase in pasture yield when legumes were oversown with grass pastures compared to grass-only pastures in the tropics [ 62 , 63 ]. The presence of 11–33% legumes in temperate pastures was found to increase DM yield, but with a reduced yield benefit as the legume proportion increased to 67% or more [ 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although Desmanthus contributed a small proportion of initial pasture biomass (11.5%) in the study, pasture DM yield was 443 kg/ha higher in the Desmanthus paddock compared to the buffel-grass-only paddock. This finding agrees with other studies that reported an increase in pasture yield when legumes were oversown with grass pastures compared to grass-only pastures in the tropics [ 62 , 63 ]. The presence of 11–33% legumes in temperate pastures was found to increase DM yield, but with a reduced yield benefit as the legume proportion increased to 67% or more [ 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…Sometimes it is also referred to as mixed cropping [41]. In pasture-based cropping system, grass-legume intercropping is an ideal example of mixed intercropping [42]. The mixed intercropping is commonly observed to fulfil the requirement of food and forage where the land resource is a limiting factor [43].…”
Section: Mixed Intercroppingmentioning
confidence: 99%
“…Sturludottir et al (2013) reported more DM production of 9, 15 and 7% in mixture plots than the most productive monoculture in the first, second and third year respectively in a study they conducted. Gulwa et al (2017) also reported higher total dry matter production in grass-legume mixture plots in comparison to grass only plots in a study that was conducted in the Eastern Cape Province, South Africa. The difference in growth patterns of legumes is reported to have a potential of leading to efficient use of resources such as light when grown in a mixture than when grown separately.…”
Section: Improved Biomass Productionmentioning
confidence: 82%